Intermittent organophosphate pesticide exposure induces hepatic injury in goats with subclinical fatty liver via immune activation and energy metabolism reprogramming - Dechun Chen; Tianjun Yang; Ting Zhao; Anzhu Li; Qingjia Lin; Xinying Zhou; Huanrong Zhang; Jian Fu; Falong Yang; Haifeng Liu (Environmental Pollution, 2026)

VMMFNet: a lightweight dual-branch multispectral fusion network for multi-stage detection of pine wilt disease - Jiajun Wang; Guanyi Cheng; Fang Wang; HongPing Zhou; Haifeng Lin (Computers and Electronics in Agriculture, 2026)

Analysis of the vibration characteristics of liquid droplets in oil induced by CPG electric field with data-driven assistance - Ye Peng; Yaozhong Hu; Haifeng Gong; Lin Yan; Bao Yu; Hong Yin; Ping Ouyang (Journal of Environmental Chemical Engineering, 2026)

Temperature-dependent migration and stabilization mechanisms of heavy metals during co-combustion of MSW with multi-source organic industrial wastes - Lin Gu; Xinchao Zhang; Meng Gong; Lexuan Wang; Wei Mao; Haifeng Wen; Jixin Li; Chenxi Liu (Journal of Environmental Chemical Engineering, 2026)

Cavity-assisted multi-interface heat management in a hollow aerogel evaporator for efficient and salt-resistant solar evaporation - Long Peng; Haifeng Zhang; Tianxiang Zhou; Mingyu Wang; Zhijian Li; Xiangxin Hou; Danyan Qin; Yi E; Xianbao Wang; Liangyou Lin (Journal of Environmental Chemical Engineering, 2026)

Average photon energy based solar spectrum reconstruction for building-oriented TMY databases - Shuo Ma; Yanyun Zhang; Jingchao Xie; Yupeng Wu; Haifeng Wu; Peng Xue; Lin Li (Journal of Cleaner Production, 2026)

The plastisphere: from microbial pollution to biodegradable solution - Wenfang Lin; Kai Yang; Tao Lu; Xiaoxi Kang; Xinyu Xing; Ewa Korzeniewska; Natalia P. Ivleva; Feng Ju; Haifeng Qian; Li Cui; Yong-guan Zhu (ENGINEERING Environment, 2026)
Microplastic pollution is threatening planetary health and sustainable development. The microbiota colonizing microplastic surfaces, termed the plastisphere, has emerged as artificial niches that harbor both microbial risks and novel biodegradation potential. However, these two aspects of the plastisphere have often been investigated in isolation. In this review, we first elaborate on how microplastics act as vectors in facilitating the enrichment and dissemination of pathogens, antibiotic resistance genes (ARGs), and even virus, thereby causing serious microbial and ecological risks, and eventually impacting human health. To address the potential risks, the key plastic-degrading resources, the underlying mechanisms, and recent advances in biodegradation technologies are synthesized. Given the dual roles of plastisphere microbes, we therefore propose a two-dimensional screening framework to identify safer and more efficient degraders. This review aims to guide the selection or synthesis of safe and highly efficient degrading microbial consortia, thereby providing sustainable and eco-friendly strategies for mitigating plastic pollution.

Oxygen-driven shift from Pb(II) lattice incorporation to reversible surface complexation: Exploiting hydrothermal sludge DOM for high-purity vivianite recovery - Xin Wang; Chaoyue Tai; Lexuan Wang; Yuanyuan Pei; Zhehao Li; Yiyang He; Suyun Xu; Lin Gu; Hanlin Zhang; Haiping Yuan; Haifeng Wen (Water Research, 2026)

Co-pyrolyzed biochar enhances soil fertility and crop quality by modulating rhizosphere microbial functional modules - Zhouyang Lin; Jiaqi Li; Yaquan Zhang; Yi Lu; Qingyun Chen; Shengdao Shan; Haifeng Zhuang; Jianzhou Fu (Journal of Soils and Sediments, 2026)

Self-adaptive heat control in honeycomb matrices for sustainable desalination and adsorptive lithium recovery - Haifeng Zhang; Zhijian Li; Tianxiang Zhou; Long Peng; Mingyu Wang; Liangyou Lin; Xianbao Wang (Desalination, 2026)

PRMT1-rich exosomes derived from M2 macrophages as novel therapeutics for enhancing fracture healing - Haifeng Hong; Cuiyun Zhou; Haibing Wang; Changhui Lin; Min Fang; Juntian Liu; Minhui Yang (Tissue and Cell, 2026)

Degradation of bisphenol A using a three-dimensional electrochemical reactor: Synergistic effects of H2O2 and mechanistic insights - Xu Ren; Lin Chen; Haifeng Fu; Meng Shen; Kai Song; Qiang Ma; Xin Peng (Process Safety and Environmental Protection, 2026)

From gene to function: GABA receptor-associated protein (GABARAP) interacts with and potentiates the GABA receptor (RDL) in Megalurothrips usitatus (Bagnall) (Thysanoptera: Thripidae) - Haifeng Jin; Yonghui Lin; Sumit Singh; Yuran Xie; Wayne Jiang; Fen Li; Shaoying Wu (Pesticide Biochemistry and Physiology, 2026)

Citral-loaded PVA-PVP hydrogel pad: Preparation, physicochemical properties, characterization, and application for blueberry preservation - Haifeng Rong; Wenna Li; Yuxuan Li; Sixu Lin; Runan Zhao; Yufeng Xu; Bingxin Sun; Yunhe Zhang; Xuerui Yan (Food Packaging and Shelf Life, 2026)

Development and evaluation of an aquatic earthworm cultivation system for simultaneous waste activated sludge reduction and biomass upgrading - Yupeng Du; Ziyi Duan; Lin Li; Chao Xu; Yuchen Liu; Dong-Hoon Kim; Sang-Hyoun Kim; Haifeng Zhang; Harsha Ratnaweera; Xueqing Shi (Bioresource Technology Reports, 2026)

Machine learning-enhanced UAV multispectral remote sensing for monitoring rice leaf area index across critical growth stages - Chao Su; Zaiying Ling; Liwang Han; Yanmin Shuai; Jianguang Wen; Xingwen Lin; Haifeng Tang; Alexandre Maniçoba da Rosa Ferraz Jardim; Hoi Leong Lee; Xuguang Tang (Precision Agriculture, 2026)

Biological Evaluation and Molecular Docking of Extracts from the Dinoflagellate Amphidinium carterae - Nedaa Ahmed; Mohamed A. M. El-Tabakh; Xihuang Lin; Cifu Lin; Feifei Pan; Haifeng Gu (Journal of Ocean University of China, 2026)

Waste activated sludge derived biopolymer amelioration for desert sand: Impact on moisture retention, vegetation growth and microbial community - Sudan Lin; Yujiao Zhang; Xinxin Zong; Chao Xu; Lin Li; Haifeng Zhang; Dong-Hoon Kim; Boyan Xu; Ratnaweera Harsha; Xueqing Shi (Journal of Cleaner Production, 2026)

Site cooperation of copper-silica interfacial Cu+/Cuσ+ species boosts low-temperature chemoselective hydrogenation of functionalized nitroarenes - Guang Xian Pei; Mengdi Guo; Lin Li; Hong Wen Guo; Haifeng Qi; Haisheng Wei; Xiao Yan Liu; Yousheng Yin (Chemical Engineering Journal, 2026)

Robust high-temperature macroscale superlubricity enabled by interface engineering of boronized surfaces and hydroxyl-rich polyol lubricants - Yixuan Zhang; Hongxing Wu; Hang Li; Lin Wang; Junqin Shi; Ke Hua; Haifeng Wang; Feng Zhou; Weimin Liu (Science Bulletin, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Adaptive multi-objective optimization of thermal and perceptual livability in high-density residential environments using image-based spatial metrics - Xudong Zhang; Weiyi Jia; Haifeng Diao; Taihan Chen; Ziyuan Zhang; Ervine Shengwei Lin; Zhiqiang Wu (Building and Environment, 2026)

Spatiotemporal characteristics of the vehicle-cabin thermal environment and occupant thermal responses under strong summer solar radiation - Yuxin Yang; Rui Zhao; Juan Yu; Deyin Zhang; Borong Lin; Kaiyue Ma; Xi Zhang; Haifeng Xia (Building and Environment, 2026)

Euphorbia diterpenoids from Euphorbia peplus possessing anti-Alzheimer's activity via targeting PPARγ and upregulating the level of ABCA1 - Yanlan Yang; Shoulun He; Yingting Lin; Junjie Chen; Renjing Yang; Xueli Li; Jingyu Sun; Guanghui Wang; Wenjing Tian; Haifeng Chen (Phytochemistry, 2026)

Hierarchical attention and feature enhancement network for multi-scale small targets in pine wilt disease - Jiajun Wang; Li Jin; Fang Wang; Hongping Zhou; Haifeng Lin (Computers and Electronics in Agriculture, 2025)

PWD-lightweight and feature fusion network for multi-stage joint detection of pine wilt disease - Jie Zhou; Fang Wang; Hongping Zhou; Haifeng Lin (Computers and Electronics in Agriculture, 2025)

A novel carbon-negative side-stream MBMBR process for municipal wastewater reclamation driven by biopolymer and nutrient recovery - Haifeng Zhang; Yi Zhang; Lin Li; Changqing Liu; Shujuan Huang; Tong Yu; Dong-Hoon Kim; Seoktae Kang; Boyan Xu; Xueqing Shi; How Yong Ng (Water Research, 2025)

Electrochemical advanced oxidation processes for treating wastewater containing tetracycline antibiotics: Methods, mechanisms, and perspectives - Lin Chen; Haifeng Fu; Xu Ren; Yinqi Chen; Kai Song; Xinjie Cheng; Yong Liu (Journal of Environmental Chemical Engineering, 2025)

Synergistic Fe single-atom/amorphous Fe oxide on carbon nitride directs efficient peroxymonosulfate activation for non-radical phenolic pollutants degradation - Juan Liu; Yu Zhang; Jianyang Gao; Haifeng Lin; Lei Wang; Jixiang Xu (Chemical Engineering Journal, 2025)

Correction: Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2025)

High acyl gellan oligosaccharides trigger jasmonic acid-mediated immunity in Arabidopsis thaliana: Structural characterization and defense activation - Shousen Guo; Chen Zhao; Haifeng Ni; Kunlun Li; Song Zhang; Le Su; Qiulin Yue; Lin Zhao (Physiological and Molecular Plant Pathology, 2025)

HTEM: High-throughput toolkit for elasticity modeling - Zhen Yang; Jiawei Xian; Yuanji Xu; De-Ye Lin; Qingchun Wang; Xingyu Gao; Fuyang Tian; Haifeng Song (Computer Physics Communications, 2025)

The effect of construction measures on the seismic performance of a frame-infilled wall with fabricated constructional column - Shucheng Yuan; Haifeng Lin; Haibo Luo; Zhanyuan Zhu; Zuyin Zou; Wei Liang; Zhuoying Wang; Bing Ma; Jinxin Yao; Qichao Zhang; Jiangfeng Dong; Hwa Kian Chai (Bulletin of Earthquake Engineering, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Human umbilical cord mesenchymal stem cell-derived exosomes repair raloxifene-induced damage in endometrial stromal cells via autophagy activation - Shiling Chen; Xiuying Lin; Lei Liu; Jianhua Fu; Xiaodan Lu; Chunxue Niu; Qilai Wang; HaiFeng Wei; Mengxue Wu; Munan Sun; Lixin Cao; Xuguang Mi; et al. (Reproductive Toxicology, 2025)

Efficient NMR spectroscopy approach for the determination of the relative configuration of Δ5,6Δ11,12-jatrophane diterpenes and their chemotherapy sensitization activities - Wenjing Tian; Jie Li; Mi Zhou; Yanlan Yang; Yingting Lin; Guanghui Wang; Zhiping Zeng; Yuting Bian; Cuiling Sun; Rong Ding; Haifeng Chen (Phytochemistry, 2025)

Intestinal barrier disruption by cadmium and microplastics: Mechanistic insights from integrated metabolomic and proteomic analysis in mice - Jiajie Yang; Danni Wang; Junyu Huang; Ting Zhao; Maoting Chen; Shengxuan Lin; Xinqi Yu; Falong Yang; Haifeng Liu; Shiwen Xu; Dechun Chen (Environmental Pollution, 2025)

Engineered honeysuckle extracellular vesicles loaded in ROS response hydrogel for inhibition of postoperative abdominal adhesion - Xiaolin Pan; Panyong Zhu; Yanwen Ding; Chenna Di; Zhe Yang; Haifeng Zhou; Chengwei Li; Lin Jin (Chemical Engineering Journal, 2025)

Unveiling a two-stage closed-pore formation mechanism in bamboo-derived hard carbons for high-plateau-capacity sodium-ion battery anodes - Zhenbing Sun; Zhenrui Li; Yujun Li; Zhihui Wang; Haifeng Zuo; Lin Zhao; Xinge Liu (Chemical Engineering Journal, 2025)

Mobile measurements of atmospheric isoprene across subtropical forests in Southern China - Haifeng Yu; Xiangcheng Wu; Lin Cheng; Wen Tan; Liang Zhu; Yunhua Chang (Atmospheric Environment, 2025)

Atmospheric emerging pollutants of cyclic volatile methyl siloxanes across the Yangtze River Delta region revealed by mobile measurements - Lin Cheng; Yunhua Chang; Haifeng Yu; Xiang Che; Wen Tan; Liang Zhu (Chemosphere, 2025)

Impact of dietary sorghum inclusion on growth, intestinal microbiome, liver function, and muscle quality in juvenile Nile tilapia (Oreochromis niloticus) - Xiangqin Lin; Xuehan Wang; Xiaoxue Meng; Beiping Tan; Lu Zhang; Haifeng Mi; Junming Deng (Aquaculture, 2025)

Hydrogel pads loaded with essential oil contribute to maintaining blueberry quality after transportation - Yuxuan Li; Haifeng Rong; Sixu Lin; Yaohui Zheng; Ling Yang; Bingxin Sun; Yunhe Zhang; Yufeng Xu; Xuerui Yan (Food Packaging and Shelf Life, 2025)

The ecosystem-based marine comprehensive zoning practice and evaluation: A case study of Nantong, China - Zhou Chen; Haifeng Zhang; Lin Zhao; Wen Du; Min Xu (Ecological Engineering, 2025)

Hollow p-n heterostructures with vacancy engineering to enhance Z-scheme photocatalytic CO2 reduction - Zhitao Zou; Yaxin Wang; Tianyi Zhang; Jing Lu; Vladimir Turkevich; Yueqin Yu; Jixiang Xu; Haifeng Lin; Yanyan Li; Lei Wang (Chemical Engineering Journal, 2025)

Edge-electron induced ferrimagnetic effect to accelerate interfacial desolvation kinetics toward dendrite-free Zn metal batteries - Haifeng Yang; Fangqi Liu; Bixian Chen; Xiaomin Cheng; Qinghua Guan; Jing Dong; Teng Li; Lujie Jia; Wenbin Wang; Jing Zhang; Jiqiang Jia; Yongzheng Zhang; et al. (Chemical Engineering Journal, 2025)

Thermal hydrolysis-induced molecular transformations in sludge: Implications for photochemical reactivity and dissolved antibiotics photodissipation - Haifeng Wen; Xin Wang; Xinchao Zhang; Yiyang He; Lin Gu; Hanlin Zhang; Peize Wu (Journal of Hazardous Materials, 2025)

Ordered mortality of mangroves under extreme flooding in a tropical microtidal estuarine lagoon in China - Lin Zhang; Haifeng Fu; Mao Wang; Wenqing Wang (Estuarine, Coastal and Shelf Science, 2025)

Anaerobic treatment of wastewater using a multistage anaerobic reactor (MAR) under low temperature and tetracycline stress - Huige Xing; Lin Zhao; Zhaojing Qian; Jie He; Haifeng Lu; Weizhong Jiang; Buchun Si (Chemical Engineering Journal, 2025)

Comparative study on combustion characteristics of biomass digestate-derived pyrochar and hydrochar: Insights from structural composition and oxygen-containing groups - Haifeng Wen; Jixin Li; Xin Wang; Wei Mao; Yiyang He; Xiao Cao; Haiyan Yang; Junyu Zhang; Suyun Xu; Lin Gu (Fuel, 2025)

Use of non-targeted metabolomics to explore metabolic differences between stem cells and callus of Tetraena mongolica - Yeru Yang; Haihua Li; Ruiping Wang; Jiahe Li; Ling Li; Jiayu Li; Lin Ou; Jun Li; Chengbo Zhang; Liyu Wang; Fengqiang Yu; Zhi He; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Evaluation on the antiviral activity of aloe emodin against Micropterus salmoides rhabdovirus in vitro and in vivo - Yao Wang; Mengmeng Wang; Zhiyang Lin; Guangshuo Wang; Yunlong Qin; Mingzhu Liu; Fei Ling; Haifeng Jiang; Tianqiang Liu; Gaoxue Wang (Aquaculture, 2025)

Stair-Stepping metamaterial and the derived isolator for all-DOF vibrations with multi-payloads - Haifeng Ou; Jia Zeng; Minqing Lin; Yifan Wang; Yujun Zeng; Xi Fang; Lingling Hu (Engineering Structures, 2025)

Efficient Neural Network Classification of Parkinson’s Disease and Schizophrenia Using Resting-State EEG Data - Wenjing Xiong; Lin Ma; Haifeng Li (Brain Topography, 2025)

An innovative high-rate biofilm-based process: Biopolymer production and recovery from wastewater organic pollutants - Haifeng Zhang; Yi Zhang; Lin Li; Shujuan Huang; Weiwei Ma; Boyan Xu; How Yong Ng; Dong-Hoon Kim; Seoktae Kang; Xueqing Shi (Journal of Environmental Management, 2025)

PWDViTNet: A lightweight early pine wilt disease detection model based on the fusion of ViT and CNN - Zhichao Chen; Haifeng Lin; Di Bai; Jingjing Qian; Hongping Zhou; Yunya Gao (Computers and Electronics in Agriculture, 2025)

Implant coating for promoted postoperative bone regeneration via cascade Reaction-Mediated microenvironment reprogramming - Bing Yan; Rurong Lin; Chongyin Qiu; Wei Sun; Xiaogang Ma; Jianxing Huang; Shuai Liu; Haifeng Liang; Chengzhong Xu; Chunyi Pu; Xiaojing Liu; Bo Yu; et al. (Chemical Engineering Journal, 2025)

Mobile measurements of atmospheric decamethylcyclopentasiloxane (D5) in Eastern China - Haifeng Yu; Yunhua Chang; Lin Cheng; Wen Tan; Liang Zhu; Jianlin Hu (Atmospheric Environment, 2025)

Dietary lysine deficiency causes intestinal immune dysfunction partially via Janus kinases (JAKs)/signal transducers and activators of transcription (STATs) signalling pathways of on-growing grass carp (Ctenopharyngodon idella) - Yangyang Hu; Lin Feng; Weidan Jiang; Pei Wu; Yang Liu; Shengyao Kuang; Ling Tang; Lu Zhang; Haifeng Mi; Xiaoqiu Zhou (Animal Feed Science and Technology, 2025)

Insights into the synergism of Mn-doped carbon@Fe7S8/Fe2O3/Fe derived from MIL-88A(Fe) in activating peroxymonosulfate and degrading ciprofloxacin: Accelerating superoxide radicals generation - Jianyang Gao; Hengyi Xie; Jing Wu; Haifeng Lin; Jun Xing; Jixiang Xu; Fusheng Liu; Volodymyr Turkevych; Lei Wang (Chemical Engineering Journal, 2025)

Genetic patchiness of the endangered giant clam Tridacna maxima from Peninsular Malaysia - Li Keat Lee; Ya Yi Huang; Chaolun Allen Chen; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Coral Reefs, 2025)

Study of the Drug Resistance Function of Ivermectin-Resistance-Related miRNAs in Haemonchus contortus - HaiFeng Wen; YanMin Zhang; Lin Yang; WenLong Wang; ChunXia Liu (Acta Parasitologica, 2025)

Microfluidic-engineered portable microsphere sensors for multi-mycotoxins detection - Xiaorui Wang; Gaowa Xing; Zengnan Wu; Haifeng Lin; Yongning Lin; Jiaxu Lin; Yaoshuang Xie; Wenjun Liao; Ling Lin (Chemical Engineering Journal, 2025)

First direct measurements of the nitrogen isotopic composition of vehicle tailpipe-emitted NH3 and implications for the source apportionment of NH3 in urban atmosphere - Yu-Ning Feng; Yunhua Chang; Lin Cheng; Haifeng Yu; Jinling Lv; Wendell W. Walters (Science of The Total Environment, 2024)

A macro-level life cycle environmental-economic impact and benefit assessment of sponge cities in China - Changqing Xu; Wei Lin; Yifei Zhu; Bin Zhang; Zhaohua Wang; Haifeng Jia (Resources, Conservation and Recycling, 2024)

The combination of HSI and NMR techniques with deep learning for identification of geographical origin and GI markers of Lycium barbarum L. - Chengcheng He; Xin Shi; Haifeng Lin; Quanquan Li; Feng Xia; Guiping Shen; Jianghua Feng (Food Chemistry, 2024)

The nexus of solar absorption and morphology designs based on 2D photothermal materials: From rational design to advanced application of water purification - Tingting Jiang; Sihui Bian; Yu Wang; Xiaorui Fan; Lin Zhu; Xinyue Song; Guanbo wang; Tianhao Wang; Haifeng Zhang (Chemical Engineering Journal, 2024)

Oxygen vacancies engineering in Mn3O4 for regulating peroxymonosulfate activation and efficient bisphenol A degradation - Jing Wu; Hengyi Xie; Gangsheng Zhang; Haifeng Lin; Jun Xing; Lei Wang; Jixiang Xu (Chemical Engineering Journal, 2024)

Research on the shallow landslide stability of vegetated slopes with expansive soils based on root morphology - Yalong Li; Guolin Yang; Yuliang Lin; Tianyu Zhao; Ruikai Duan; Haifeng Li (Ecological Modelling, 2024)

Ordered 2D/3D CoNi-LDH/FeSe electrode for efficient and durable seawater oxidation - Yue Shi; Jiejie Bai; Aixin Ma; Zhitao Zou; Yanru Liu; Haifeng Lin; Dehong Chen; Ruiyong Zhang; Jianping Lai; Lei Wang (Chemical Engineering Journal, 2024)

Bio-refinery of organic pollutants for wastewater reclamation - Haifeng Zhang; Yi Zhang; Sudan Lin; Xuejun Bi; Shujuan Huang; Bo Jiang; Dong-Hoon Kim; How Yong Ng; Xueqing Shi (Chemical Engineering Journal, 2024)

Aerobic granular sludge inoculant for enhancing high salinity wastewater treatment: Performance and value-added biopolymer recovery - Haifeng Zhang; Shuning Wang; Sudan Lin; Yuanyuan Miao; Dong-Hoon Kim; Boyan Xu; Wenfeng Du; Xueqing Shi; Shujuan Huang (Chemical Engineering Journal, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Vanishing giants: An assessment on the population status of giant clams across Malaysia - Li Keat Lee; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Chaolun Allen Chen; Po Teen Lim; Chui Pin Leaw (Regional Studies in Marine Science, 2024)

Mechanistic insights into temperature-driven retention and speciation changes of heavy metals (HMs) in ash residues from Co-combustion of refuse-derived fuel (RDF) and red mud - Haifeng Wen; Jingjing Gao; Xin Wang; Yiyang He; Jixin Li; Lin Gu; Ziyu Zhao; Haixiang Yu; Suyun Xu (Journal of Environmental Management, 2024)

Dynamically crosslinked chiral optics sensing for ultra-sensitive VOCs detection - Shuaiqi Wang; Guomin Zhao; Yihan Zeng; Haifeng Lin; Bingqun Lin; Mingzhu Pan (Chemosphere, 2024)

Facile synthesis of polymer-derived K, Ti co-doped Li4SiO4-based sorbent for efficient and stable post-combustion CO2 capture - Liang Cai; Haifeng Xue; Xiuhong Yang; Yitong Lin; Xin Hu; Yingchun Zhang (Chemical Engineering Journal, 2024)

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

Nanoarchitectonics of ternary Zn-Mn-Co oxides for efficient peroxymonosulfate activation and antibiotics degradation via accelerating electron transfer - Hengyi Xie; Gangsheng Zhang; Jixiang Xu; Haifeng Lin; Lei Wang (Journal of Environmental Chemical Engineering, 2024)

IL-22 promotes occludin expression by activating autophagy and treats ulcerative colitis - Hui Nong; Haifeng Yuan; Yiting Lin; Siyu Chen; Yanbo Li; Zhaoqiong Luo; Wen Yang; Tao Zhang; Yuanneng Chen (Molecular and Cellular Biochemistry, 2024)

Penetration Characteristics of Mono-Column Composite Bucket Foundation for Offshore Wind Turbines - Jiandong Xiao; Xiaoqiang Gu; Yifeng Lin; Haifeng Cheng; Xin Qi; Puyang Zhang; Shuyang Wang (Journal of Marine Science and Engineering, 2024)
To address the issue of seepage and soil plugging during the sinking of mono-column composite bucket foundations (MCCBFs), experiments were conducted on the installation of foundations under a variety of complex geological conditions. The effect of negative pressure sinking mode on the foundation’s seepage field was analyzed, the formation mechanism of soil plugging in sand was explained, and an efficient method for calculating the height of soil plugging was proposed in conjunction with these investigations. The findings demonstrate that the finite element method simulation of the soil’s seepage field is the most accurate, that the pumping volume of the foundation during sinking through is high, that the formation of the soil plug height is high, and that clear depressions can be seen on the foundation manifold’s exterior. The equation presented in this study makes it easier to forecast the height of a foundation plug and can offer direction for engineering design.

Tree species, mycorrhizal associations, and land-use history as drivers of cohesion in soil biota communities and microbe-fauna interactions - Petr Heděnec; Hanan Almahasheer; Qiang Lin; Yan Peng; Haifeng Zheng; David Pessanha Siqueira; Kai Yue; Umar Hussaini bin Tarmizi; Mohamad Aqmal-Naser; Siti Norasikin Ismail; Amirah Alias; Johannes Rousk; et al. (Forest Ecology and Management, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Will the Globe Encounter the Warmest Winter after the Hottest Summer in 2023? - Fei Zheng; Shuai Hu; Jiehua Ma; Lin Wang; Kexin Li; Bo Wu; Qing Bao; Jingbei Peng; Chaofan Li; Haifeng Zong; Yao Yao; Baoqiang Tian; et al. (Advances in Atmospheric Sciences, 2024)

FireViTNet: A hybrid model integrating ViT and CNNs for forest fire segmentation - Guodong Wang; Di Bai; Haifeng Lin; Hongping Zhou; Jingjing Qian (Computers and Electronics in Agriculture, 2024)

Physical drivers of Noctiluca scintillans (Dinophyceae) blooms outbreak in the northern Taiwan Strait: A numerical study - Zhonghao Lin; Peng Zhan; Jianping Li; Jun Sasaki; Zhongfeng Qiu; Chun Chen; Shuangyan Zou; Xiaotong Yang; Haifeng Gu (Harmful Algae, 2024)

Efficient carbon dioxide adsorption properties of cellular structure Li4SiO4 sorbents prepared by additive manufacturing based on polymer-derived ceramics strategy - Liang Cai; Guangfan Tan; Xiuhong Yang; Haifeng Xue; Yitong Lin; Xin Hu; Zhuoyuan Song; Yingchun Zhang (Chemical Engineering Journal, 2024)

Evaluation of the dietary L-valine on fish growth and intestinal health after infection with Aeromonas veronii - Quanquan Cao; Ju Zhao; Lingjie He; Tianran Zhang; Lin Feng; Weidan Jiang; Pei Wu; Juan Zhao; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Vitamin D3 activates the innate immune response and xenophagy against Nocardia seriolae through the VD receptor in liver of largemouth bass (Micropterus salmoides) - Quanquan Cao; Ju Zhao; Mingyao Yan; Zhong Luo; Fu Luo; Lin Feng; Weidan Jiang; Pei Wu; Yan Wang; Debin Li; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Preparation of refined phosphoric acid with recycling of raffinate acid by the extraction of metal impurities - Xiaokang Gong; Chao Hu; Yanru Jin; Haifeng Liu; Jiahui Bai; Lixue Niu; Lin Yang (Journal of Cleaner Production, 2024)

Development of nucleic acid extraction and real-time recombinase polymerase amplification (RPA) assay integrated microfluidic biosensor for multiplex detection of foodborne bacteria - Yuting Shang; Gaowa Xing; Haifeng Lin; Yucheng Sun; Shulang Chen; Jin-Ming Lin (Food Control, 2024)

The mediating effect of perceived stress on the relationship between big five personality traits and suboptimal health status in Chinese population: a nationwide survey in the framework of predictive, preventive, and personalized medicine - Qihua Guan; Hualei Dong; Zhihui Zhang; Zheng Guo; Zi Lin; Hui Niu; Yibo Wu; Haifeng Hou (EPMA Journal, 2023)

Effect of red mud on combustion behavior and heavy metal stabilization of Refuse Derived Fuel (RDF) - Haifeng Wen; Jingjing Gao; Yao Yang; Min Zhao; Lin Gu; Haixiang Yu; Entong Liu (Journal of Environmental Chemical Engineering, 2023)

ZnFexAl2-xO4 spinel supported PdZnβ bifunctional catalyst for methanol steam reforming - Lina Zhang; Jianhuang Wang; Baoquan Zhang; Zenan Lin; Lele Liu; Xianhua Zhang; Shuai Wang; Jingdong Lin; Haifeng Xiong; Chuanqiang Wu; Yong Wang; Shaolong Wan (Chemical Engineering Journal, 2023)

Repairing vacancy defects for stabilization of high surface area hexagonal boron nitride under harsh conditions - Jinshu Tian; Jian Guan; Mingliang Xu; Shuya Qian; Kai Ma; Shaolong Wan; Zhaoxia Zhang; Haifeng Xiong; Shuai Wang; Yong Wang; Jingdong Lin (Chemical Engineering Journal, 2023)

Pd decorated MoS2 nanoflowers as photothermal catalyst for enhanced NIR-induced 4-nitrophenol reduction - Hanhan Lv; Min Lin; Chiyan Yu; Haifeng Wang; Maoquan Li; Lisha Zhang; Zixiao Liu; Zhigang Chen (Journal of Environmental Chemical Engineering, 2023)

Sulfide S-Zn-Cd isotopes and origin of the Liangyan Zn-Pb deposit in the Sichuan-Yunnan-Guizhou metallogenic province, SW China - Tao Wu; Yufan He; Zhiwei He; Zhilong Huang; Lin Ye; Chen Wei; Fan Haifeng; Yusi Hu; Lin Du; Minshan Gun (Journal of Asian Earth Sciences, 2023)

Excessive dietary soluble arabinoxylan impairs the intestinal physical and immunological barriers via activating MAPK/NF-κB signaling pathway in rainbow trout (Oncorhynchus mykiss) - Junming Deng; Xindang Zhang; Beibei Lin; Haifeng Mi; Lu Zhang (Fish & Shellfish Immunology, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

A novel approach to reducing the biological toxicity of shale gas fracturing flowback fluid through recycling of high-value nano-BaSO4 - HaiFeng Su; JiaFu Lin; Qiao Chen; ChangQiang Wu; FengLin Xu (Journal of Cleaner Production, 2023)

V-ATPase V0 subunit activation mediates maduramicin-induced methuosis through blocking endolysosomal trafficking in vitro and in vivo - Yuling Zheng; Jing Xiao; Junqi Wang; Bin Dong; Dawei Guo; Hui Ji; Haifeng Sun; Lin Peng; Shanxiang Jiang; Xiuge Gao (Food and Chemical Toxicology, 2023)

Multiscale Transport Characteristics of Coalbed Methane in Abandoned Mines and Its Applications in Gas Recovery - Kang Yang; Wei Li; Lin Gao; Haifeng Wang; Jinzhao Liu; Jia Lin (Natural Resources Research, 2023)

Unique porous ZnS-CdS-CoSx Reuleaux triangle nanosheets: Highly promoted visible-light photocatalytic H2 evolution via synergistic effect of Z-scheme heterojunction and vacancy defects - Liping Wang; Yanyan Li; Hanchu Chen; Ying Zuo; Hui Wang; Jixiang Xu; Haijiao Xie; Haifeng Lin; Lei Wang (Fuel, 2023)

Novel Y2O3 based calcium-alginate beads for highly selective adsorption of phosphate from aqueous solution - Sudan Lin; Yongzhi Xu; Chen Fu; Haifeng Zhang; Qiaoping Kong; Haoran He; Siyuan Liu; Xueqing Shi; Dandan Zhao (Environmental Science and Pollution Research, 2023)

Preparation of multi-layered microcapsule-shaped activated biomass carbon with ultrahigh surface area from bamboo parenchyma cells for energy storage and cationic dyes removal - Yao Xia; Haifeng Zuo; Jialin Lv; Siyuan Wei; Yuxuan Yao; Zhigao Liu; Qiuqin Lin; Yanglun Yu; Wenji Yu; Yuxiang Huang (Journal of Cleaner Production, 2023)

ZIF-67/melamine derived hollow N-doped carbon/Co9S8 polyhedron to activate peroxymonosulfate for degradation of tetracycline - Gangsheng Zhang; Jianyang Gao; Jing Wang; Haifeng Lin; Jixiang Xu; Lei Wang (Journal of Environmental Chemical Engineering, 2023)

Can Eurasia Experience a Cold Winter under a Third-Year La Niña in 2022/23? - Fei Zheng; Bo Wu; Lin Wang; Jingbei Peng; Yao Yao; Haifeng Zong; Qing Bao; Jiehua Ma; Shuai Hu; Haolan Ren; Tingwei Cao; Renping Lin; et al. (Advances in Atmospheric Sciences, 2023)

FENet: feature enhancement network for land cover classification - Zhanming Ma; Min Xia; Haifeng Lin; Ming Qian; Yonghong Zhang (International Journal of Remote Sensing, 2023)

The mechanism of different cyanobacterial responses to glyphosate - Wei Lin; Zhenyan Zhang; Yiling Chen; Qi Zhang; Mingjing Ke; Tao Lu; Haifeng Qian (Journal of Environmental Sciences, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Ancient and modern mitogenomes of red deer reveal its evolutionary history in northern China - Bo Xiao; Tianjiao Wang; Adrian M. Lister; Junxia Yuan; Jiaming Hu; Shiwen Song; Haifeng Lin; Siren Wang; Chunxue Wang; Dong Wei; Xulong Lai; Xiumei Xing; et al. (Quaternary Science Reviews, 2023)

Synthetic aperture radar image despeckling neural network based on maximum a posteriori probability estimation - Yuting Zhu; Mingrui Chen; Xiaoqing Wang; Baihong Lin; Haifeng Huang (International Journal of Remote Sensing, 2023)

Two new cycloartane triterpenoid glycosides from the rhizomes of Actaea vaginata - Shunqin Zeng; Xiangyuan Li; Zixuan Zhao; Yan Lin; Yindi Zhu; Guoxu Ma; Xiaohong Zhao; Xudong Xu; Meichun Wu; Haifeng Wu; Qiongyu Zou; Yongtao Li (Natural Product Research, 2023)

Effective multipurpose sewage sludge and food waste reduction strategies: A focus on recent advances and future perspectives - Xuefeng Zhu; Yuting Xu; Guangyin Zhen; Xueqin Lu; Suyun Xu; Jie Zhang; Lin Gu; Haifeng Wen; Hongbo Liu; Xuedong Zhang; Zhichao Wu (Chemosphere, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Occurrence, controlling factors and noncarcinogenic risk assessment based on Monte Carlo simulation of fluoride in mid-layer groundwater of Huaibei mining area, North China - Huili Qiu; Herong Gui; Haifeng Xu; Lin Cui; Hao Yu (Science of The Total Environment, 2023)

Tree species traits and mycorrhizal association shape soil microbial communities via litter quality and species mediated soil properties - Petr Heděnec; Haifeng Zheng; David Pessanha Siqueira; Qiang Lin; Yan Peng; Inger Kappel Schmidt; Tobias Guldberg Frøslev; Rasmus Kjøller; Johannes Rousk; Lars Vesterdal (Forest Ecology and Management, 2023)

Absorption behavior of polycarboxylate superplasticizer with different molecular structures on montmorillonite - Haifeng Yang; Mingyi Li; Lisha Pan; Ping Zhang; Rami Adel Pashameah; Hala M. Abo-Dief; Shuying Xu; Chang Lin; Hassan Algadi; Jiacheng Li; Qinglong Jiang; Zhanhu Guo (Environmental Research, 2023)

7-Hydroxy questin, a new anthraquinone from a wetland fungus Aspergillus flavipes PJ03-11 - Chong Yu; Shuang Lin; Xiaorui Ma; Jie Zhang; Caixia Wu; Ben Ma; Haifeng Wang; Yuehu Pei (Natural Product Research, 2022)

SGBNet: An Ultra Light-weight Network for Real-time Semantic Segmentation of Land Cover - Kai Pang; Liguo Weng; Yonghong Zhang; Jia Liu; Haifeng Lin; Min Xia (International Journal of Remote Sensing, 2022)

Cloud/shadow segmentation based on multi-level feature enhanced network for remote sensing imagery - Shoukuan Miao; Min Xia; Ming Qian; Yonghong Zhang; Jia Liu; Haifeng Lin (International Journal of Remote Sensing, 2022)

Heavy metal-induced lipogenic gene aberration, lipid dysregulation and obesogenic effect: a review - Yang Zhou; Frank Peprah Addai; Xinshuang Zhang; Yuelin Liu; Yinfeng Wang; Feng Lin; Alex Tuffour; Jie Gu; Guangxiang Liu; Haifeng Shi (Environmental Chemistry Letters, 2022)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Size-dependent spatio-temporal dynamics of eukaryotic plankton community near nuclear power plant in Beibu Gulf, China - Lizhou Lin; Haifeng Gu; Zhaohe Luo; Na Wang (Journal of Oceanology and Limnology, 2021)

Neuroprotective Effects of 2-Substituted 1, 3-Selenazole Amide Derivatives on Amyloid-Beta-Induced Toxicity in a Transgenic Caenorhabditis Elegans Model of Alzheimer’s Disease - Huiying Wang; Yuandong Yue; Haifeng Zhao; Hao Wu; Kai Jiang; Shuang Li; Meihua Zhao; Feng Lin (Neurotoxicity Research, 2021)

A new phenolic glycoside from Trollius chinensis Bunge with anti-inflammatory and antibacterial activities - Jie Feng; Danyang Zhao; Qiannan Xu; Xiangzhong Liu; Mi Zhou; Xiansheng Ye; Ting Lin; Guanghui Wang; Cuiling Sun; Rong Ding; Wenjing Tian; Haifeng Chen (Natural Product Research, 2020)

Transcriptome analysis of strawberry fruit in response to exogenous arginine - Jinhua Lv; Qianqian Pang; Xueqin Chen; Teng Li; Jinggui Fang; Shaoyan Lin; Haifeng Jia (Planta, 2020)

Multi-Visual Feature Saliency Detection for Sea-Surface Targets through Improved Sea-Sky-Line Detection - Chang Lin; Wu Chen; Haifeng Zhou (Journal of Marine Science and Engineering, 2020)
To visually detect sea-surface targets, the objects of interest must be effectively and rapidly isolated from the background of sea-surface images. In contrast to traditional image detection methods, which employ a single visual feature, this paper proposes a significance detection algorithm based on the fusion of multi-visual features after detecting the sea-sky-lines. The gradient edges of the sea-surface images are enhanced using a Gaussian low-pass filter to eliminate the effect of the image gradients pertaining to the clouds, wave points, and illumination. The potential region and points of the sea-sky-line are identified. The sea-sky-line is fitted through polynomial iterations to obtain a sea-surface image containing the target object. The saliency subgraphs of the high and low frequency, gradient texture, luminance, and color antagonism features are fused to obtain an integrated saliency map of the sea-surface image. The saliency target area of the sea surface is segmented. The effectiveness of the proposed method was verified. The average detection rate and time for the sea-sky-line detection were 96.3% and 1.05 fps, respectively. The proposed method outperformed the existing saliency models on the marine obstacle detection dataset and Singapore maritime dataset, with mean absolute errors of 0.075 and 0.051, respectively.

Long-term influence of maize stover and its derived biochar on soil structure and organo-mineral complexes in Northeast China - Qiang Sun; Jun Meng; Binoy Sarkar; Yu Lan; Li Lin; Haifeng Li; Xu Yang; Tiexin Yang; Wenfu Chen; Hailong Wang (Environmental Science and Pollution Research, 2020)

Graphitic carbon nitride–doped sewage sludge as a novel material for photodegradation of Eriochrome Black T - Lin Gu; Guangxia Dong; Haixiang Yu; Xingbo Qiao; Kai Zhang; Xiangyu Lu; Haifeng Wen (Environmental Science and Pollution Research, 2020)

Enriching the Production of 2-Methyl-1-Butanol in Fermentation Process Using Corynebacterium crenatum - HaiFeng Su; Hua Chen; JiaFu Lin (Current Microbiology, 2020)

The mixing of multi-source fluids in the Wusihe Zn–Pb ore deposit in Sichuan Province, Southwestern China - Hongjie Zhang; Haifeng Fan; Chaoyi Xiao; Hanjie Wen; Lin Ye; Zhilong Huang; Jiaxi Zhou; Qingjun Guo (Acta Geochimica, 2019)

Genomic and Allelic Analyses of Laccase Genes in Sugarcane (Saccharum spontaneum L.) - Wenping Zhang; Jishan Lin; Fei Dong; Qing Ma; Songlin Wu; Xinyi Ma; Mahpara Fatima; Haifeng Jia; Ray Ming (Tropical Plant Biology, 2019)

Identification and Expression Analysis of TCP Genes in Saccharum spontaneum L - Jishan Lin; Mengting Zhu; Mingxing Cai; Wenping Zhang; Mahpara Fatima; Haifeng Jia; Feifei Li; Ray Ming (Tropical Plant Biology, 2019)

Effects of IPT or NDGA Application on ABA Metabolism and Maturation in Grape Berries - Hong Lin; Shanshan Wang; Takanori Saito; Katsuya Ohkawa; Hitoshi Ohara; Ampa Kongsuwan; Haifeng Jia; Yinshan Guo; Hiroyuki Tomiyama; Satoru Kondo (Journal of Plant Growth Regulation, 2018)

The ethylene response factor MdERF1B regulates anthocyanin and proanthocyanidin biosynthesis in apple - Jing Zhang; Haifeng Xu; Nan Wang; Shenghui Jiang; Hongcheng Fang; Zongying Zhang; Guanxian Yang; Yicheng Wang; Mengyu Su; Lin Xu; Xuesen Chen (Plant Molecular Biology, 2018)

Nitrogen Affects Anthocyanin Biosynthesis by Regulating MdLOB52 Downstream of MdARF19 in Callus Cultures of Red-Fleshed Apple (Malus sieversii f. niedzwetzkyana) - Yicheng Wang; Nan Wang; Haifeng Xu; Shenghui Jiang; Hongcheng Fang; Tianliang Zhang; Mengyu Su; Lin Xu; Zongying Zhang; Xuesen Chen (Journal of Plant Growth Regulation, 2018)

Overexpression of the transcription factor MdbHLH33 increases cold tolerance of transgenic apple callus - Haifeng Xu; Nan Wang; Yicheng Wang; Shenghui Jiang; Hongcheng Fang; Jing Zhang; Mengyu Su; Weifang Zuo; Lin Xu; Zongying Zhang; Xuesen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Factors influencing soil enzyme activity in China’s forest ecosystems - Haifeng Zheng; Yang Liu; Jian Zhang; Yamei Chen; Lin Yang; Hongjie Li; Lifeng Wang (Plant Ecology, 2018)

Unmanned aerial vehicle based remote sensing method for monitoring a steep mountainous slope in the Three Gorges Reservoir, China - Haifeng Huang; Jingjing Long; Haiyu Lin; Lei Zhang; Wu Yi; Bangjun Lei (Earth Science Informatics, 2017)

Zinc Fractional Absorption from a Representative Diet in Young Chinese Men and Women of the Shandong Rural Region - Cuiping Wang; Xinying Lin; Dongmei Guo; Lili Ding; Haifeng Guo; Guifa Xu; Xi Cui; Xia Wang (Biological Trace Element Research, 2017)

Association Between PARP1 Single Nucleotide Polymorphism and Brain Tumors - Hong Wang; Kun Zhang; Haifeng Qin; Lin Yang; Liyu Zhang; Yanyan Cao (Molecular Neurobiology, 2016)

Implication of the chemical index of alteration as a paleoclimatic perturbation indicator: an example from the lower Neoproterozoic strata of Aksu, Xinjiang, NW China - Haifeng Ding; Dongsheng Ma; Chunyan Yao; Qizhong Lin; Linhai Jing (Geosciences Journal, 2016)

Jasmonic acid involves in grape fruit ripening and resistant against Botrytis cinerea - Haifeng Jia; Cheng Zhang; Tariq Pervaiz; Pengcheng Zhao; Zhongjie Liu; Baoju Wang; Chen Wang; Lin Zhang; Jinggui Fang; Jianpu Qian (Functional & Integrative Genomics, 2016)

New magnetostratigraphic and pedostratigraphic investigations of loess deposits in north‐east China and their implications for regional environmental change during the Mid‐Pleistocene climatic transition - Lin Zeng; Huayu Lu; Shuangwen Yi; Yongxiang Li; Anqi Lv; Wenchao Zhang; Zhiwei Xu; Haifeng Wu; Han Feng; Mengchun Cui (Journal of Quaternary Science, 2016)
Little is known about the long‐term climatic evolution of north‐eastern (NE) China, because well‐preserved terrestrial paleoenvironmental archives are scarce in this vast region. The extensive loess deposits in the Chifeng region are the thickest and most complete loess–paleosol sequence in NE China, and have significant potential for reconstructing the paleoclimate of the region. Here, we present new high‐resolution magnetostratigraphic results from two loess–paleosol sections in the Chifeng region: the Sanbahuo (SBH) and Toudaojingzi (TDJZ) sections. The results demonstrate that both sections record the Brunhes normal polarity chron and the upper portion of the Matuyama reversed polarity chron. Based on these new results, the base of the TDJZ loess sequence is dated at ca. 1.22 Ma, representing the oldest known loess deposits in NE China. The initiation of loess accumulation in NE China was roughly synchronous with the large expansion of the Eurasian loess belt during the late Early Pleistocene (1.2–0.7 Ma), probably reflecting a widespread intensification of aridity in northern mid‐latitudes. We suggest that global cooling during the Mid‐Pleistocene climatic transition led to increased aridity and more favorable conditions for promoting the availability of silt for entrainment, transport and deposition.

Age and nature of Cryogenian diamictites at Aksu, Northwest China: implications for Sturtian tectonics and climate - Haifeng Ding; Dongsheng Ma; Qizhong Lin; Linhai Jing (International Geology Review, 2015)

Four-dimensional computed tomography angiography is valuable in intracranial dural arteriovenous fistula diagnosis and fistula evaluation - Xianwang Ye; Haifeng Wang; Qiuli Huang; Maoqing Jiang; Xiang Gao; Jie Zhang; Shengjun Zhou; Zhiqing Lin (Acta Neurologica Belgica, 2015)

Metabolic engineering of Escherichia coli to enhance shikimic acid production from sorbitol - Xianglei Liu; Jun Lin; Haifeng Hu; Bin Zhou; Baoquan Zhu (World Journal of Microbiology and Biotechnology, 2014)

Spatial and temporal analysis of drought risk during the crop-growing season over northeast China - Xingyang Yu; Xingyuan He; Haifeng Zheng; Ruichao Guo; Zhibin Ren; Dan Zhang; Jixiang Lin (Natural Hazards, 2014)

Involvement of Volume-Activated Chloride Channels in H2O2 Preconditioning Against Oxidant-Induced Injury Through Modulating Cell Volume Regulation Mechanisms and Membrane Permeability in PC12 Cells - Linyan Zhu; Wanhong Zuo; Haifeng Yang; Haifeng Zhang; Hai Luo; Dong Ye; Xi Lin; Jianwen Mao; Jianqiang Feng; Lixin Chen; Liwei Wang (Molecular Neurobiology, 2013)

Cell cycle-dependent subcellular distribution of ClC-3 in HeLa cells - Jianwen Mao; Xiaobo Li; Weiqiang Chen; Bin Xu; Haifeng Zhang; Hongzhi Li; Liwei Wang; Xiaobao Jin; Jiayong Zhu; Guixian lin; Weizhang Wang; Lixin Chen (Histochemistry and Cell Biology, 2012)

Analyses of gene expression and physiological changes in Microcystis aeruginosa reveal the phytotoxicities of three environmental pollutants - Haifeng Qian; Xiangjie Pan; Jun Chen; Dongming Zhou; Zuoguo Chen; Lin Zhang; Zhengwei Fu (Ecotoxicology, 2012)

ADAM17 regulates prostate cancer cell proliferation through mediating cell cycle progression by EGFR/PI3K/AKT pathway - Ping Lin; Xicai Sun; Tian Feng; Haifeng Zou; Ying Jiang; Zijun Liu; Dandan Zhao; Xiaoguang Yu (Molecular and Cellular Biochemistry, 2012)

Fluid geochemical features and preservation conditions of marine stratum in typical structure of Jianghan plain area - Guosheng Xu; Deyu Gong; Haifeng Yuan; Changhong Li; Guozhi Wang; Xiaofeng Hu; Juanhua Lin; Jianmin Zhu (Journal of Earth Science, 2011)

Effect of nonylphenol on response of physiology and photosynthesis-related gene transcription of Chlorella vulgaris - Haifeng Qian; Xiangjie Pan; Shutian Shi; Shuqiong Yu; Haiyan Jiang; Zhifan Lin; Zhengwei Fu (Environmental Monitoring and Assessment, 2011)

Fbxw8 is involved in the proliferation of human choriocarcinoma JEG-3 cells - Ping Lin; Jiejun Fu; Binjiahui Zhao; Feng Lin; Haifeng Zou; Leiyu Liu; Cheng Zhu; Hongmei Wang; Xiaoguang Yu (Molecular Biology Reports, 2011)

The effect of NF-κB pathway on proliferation and apoptosis of human umbilical vein endothelial cells induced by intermittent high glucose - Gang Chen; Yufang Chen; Haifeng Chen; Liantao Li; Jin Yao; Qiqin Jiang; Xu Lin; Junping Wen; Lixiang Lin (Molecular and Cellular Biochemistry, 2011)